Comprehensive Review of Hair Dyes: Physicochemical Aspects, Classification, Toxicity, Detection, and Treatment Methods - de Souza, João Carlos; Avelino, Elisa Raquel Anastácio Ferraz; Bessegato, Guilherme Garcia; da Costa, Rogério do Carmo Gonçalves; Carneiro, Patricia Alves; de Oliveira, Danielle Palma; Beluomini, Maísa Azevedo [UNESP]; Brito, Juliana Ferreira [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (American Chemical Society (ACS), 2025)
Hair dyes have been a significant facet of human culture and identity, evolving from ancient natural pigments to complex synthetic formulations. This comprehensive review delves into the multifaceted dimensions of hair dyes, examining their physicochemical properties, classification, toxicity, detection, and treatment methods. The review explores the historical progression and contemporary advancements in hair dye technologies, highlighting the persistent challenges posed by their environmental and health impacts. It categorizes hair dyes into vegetable, mineral, and synthetic types, further subdividing synthetic dyes into temporary, semipermanent, and permanent categories based on their durability and application methods. This review also discusses the toxicological concerns associated with hair dyes, emphasizing the acute and chronic health risks posed by ingredients such as p-phenylenediamine (PPD) and its derivatives. Analytical methods for detecting and quantifying hair dyes in various matrices are evaluated, showcasing techniques such as chromatography and spectrophotometry. Furthermore, the review addresses the environmental implications of hair dye disposal, focusing on innovative treatment approaches, including advanced oxidation processes and bioremediation strategies. By synthesizing the last 20 years of the literature, this review provides a balanced perspective on the benefits and risks associated with hair dyes, offering insights into future research directions and sustainable practices to mitigate their adverse effects on human health and the environment.